Osteoblasts Regulate the Expression of ADAMTS and MMPs in Chondrocytes through ERK Signaling Pathway - Ding, Xiao; Xiang, Wei; Meng, Defeng; Chao, Wang; Fei, Han; Wang, Weishan (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
Objective Degradative enzymes such as matrix metalloproteinase (MMP) and disintegrin metalloproteinase with platelet thrombin-sensitive protein-like motifs (ADAMTS) play a key role in the development of osteoarthritis (OA). We aimed to investigate the effects of OA subchondral osteoblasts on the expression of ADAMTS4, ADAMTS5, MMP-3, MMP-9, and MMP-13 in chondrocytes and the regulation of mitogen-activated protein kinase (MAPK) signaling pathway.Methods A rat knee OA model was constructed by cutting the anterior cruciate ligament of the knee joints, and normal rat articular cartilage chondrocytes (N-ACC), OA rat articular cartilage chondrocytes (O-ACC), normal subchondral bone osteoblasts (N-SBO), and OA subchondral bone osteoblasts (O-SBO) were isolated and extracted. The expressions of O-ACC and O-SBO COL1 and COL2 were detected respectively. Chondrocytes were identified by immunofluorescence of COL2 and toluidine blue staining, and osteoblasts were identified by COL1 immunofluorescence, alkaline phosphatase (ALP), and Alizarin Red staining. Gene expression of COL1, COL2, and aggrecan in normal chondrocytes and OA chondrocytes, and gene expression of osteoblast ALP and osteocalcin (OCN) were detected by RT-PCR to identify the two chondrocytes and the two osteoblast phenotypes. The constructing N-ACC group, O-ACC group, N-ACC + N-SBO group, N-ACC + O-SBO group, O-ACC + N-SBO group, O-ACC + O-SBO group, I + N-ACC + O-SBO group, and I + O-ACC + O-SBO group cell cultures, and the expression of ERK, ADAMTS4, ADAMTS5, MMP-3, MMP-9, and MMP-13 genes in chondrocytes cultured for 0, 24, 48, and 72 h were detected by RT-PCR. The protein expressions of pERK, ADAMTS4, ADAMTS5, MMP-3, MMP-9, and MMP-13 were detected by Western blot.ResultsConclusions
Keywords: Osteoarthritis; chondrocytes; osteoblasts; ERK signaling pathway